The Effect of Islamic Financial Literacy and Religiosity on Customers’ Saving Decisions at Islamic Banks, with Interest as A Mediating Variabel - Ainul Rokhimah; Khusnul Fikriyah (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
The purpose of this study is to analyze the influence of Islamic financial literacy and religiosity on customers’ savings decisions at Islamic banks, with interest serving as a mediating variable. This study employs a quantitative method, utilizing primary data obtained through an online questionnaire. Sampling was conducted using purposive sampling, with a total of 156 respondents. Data analysis was conducted using the SmartPLS 4.0 software. The results of this study indicate that (1) Islamic financial literacy influences customers’ savings decisions at Islamic banks, (2) religiosity influences customers’ interest in saving at Islamic banks, (3) Islamic financial literacy influences customers’ savings decisions at Islamic banks (4) religiosity influences customers’ savings decisions at Islamic banks; (5) interest influences customers’ savings decisions at Islamic banks; (6) Islamic financial literacy influences customers’ savings decisions through their interest in saving at Islamic banks; (7) religiosity influences customers’ savings decisions through their interest in saving at Islamic banks. This study is expected to provide additional insights and references for the advancement of knowledge in the field of Islamic finance, as well as serve as a basis for Islamic banks to enhance public interest and savings decisions in accordance with Sharia principles.